HUMAN PAPILLOMA VIRUS - ONCOGENIC VIRUS - A.N. Mayansky (Union of pediatricians of Russia, 2010)
The lecture is devoted to oncogenic viruses, particularly human papilloma virus. Papilloma viral infection is found in all parts of the globe and highly contagious. In addition to exhaustive current data on classification, specifics of papilloma viruses composition and epidemiology, the author describes in great detail the malignization mechanisms of papilloma viruses pockets. Also, issues of diagnostics and specific prevention and treatment of diseases caused by this virus are illustrated. Key words: oncogenic viruses, papilloma viruses, prevention, vaccination. (Pediatric Pharmacology. - 2010; 7(4):48-55)